Work Challenges, Opportunities, and Job Performance of Non-Teaching Personnel in a Private Higher Education Institution - Quezon, Marissa; Esmane, Argielyn (Journal of Interdisciplinary Perspectives, 2024)
The research aimed to investigate the relationship between work challenges and opportunities and their effect as predictors of job performance of non-teaching personnel at a Higher Education Institution (HEI) in Bacolod City. While most research on HEIs focuses on faculty and students, this study aimed to shed light on the experiences of non-teaching staff. The study examined the level of challenges, opportunities, and job performance of the respondents and the relationships among these three variables. It also sought to determine if work challenges and opportunities could predict job performance. The study used a descriptive-correlational design and selected 153 permanent non-teaching personnel, including administrative heads and support staff, who had worked for six months or longer in the HEI. The findings showed that respondents faced mild workload challenges, job-related stress, communication, and working conditions. They were provided ample opportunities for training, mentorship, and recognition of learning. Regarding performance, the respondents excelled in task, contextual, and adaptive performances. The study revealed no significant relationship between challenges and job performance. However, a significant relationship was found between the opportunities provided and job performance. Finally, the study determined that opportunities were significant predictors of job performance. In conclusion, the study suggests that when opportunities are effectively leveraged, the job performance of non-teaching personnel can be enhanced.